2016
DOI: 10.1007/s00296-016-3546-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of adult-onset Still’s disease using a Japanese administrative database

Abstract: Adult-onset Still's disease (AOSD) is a rare disease, and large epidemiological studies of this disease are limited. Furthermore, it has been difficult to show the incidence and characteristics of severe AOSD complications due to the rarity of this disease. The aim of our study was to describe the demographics of AOSD and the incidence and characteristics of severe complications. Using a large Japanese administrative database, we identified hospitalized patients with AOSD and described the demographics. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 22 publications
9
37
0
Order By: Relevance
“…An in- vestigation from Japan reported that the average age at the onset of AOSD was 38.1±14.3 years old in 1994 (47), in contrast to 46±19 years old in 2010 (44). Another report in 2016 from Japan stated that the mean onset age was 53.1± 19.6 years old (4). About 23% of cases developed it at !…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An in- vestigation from Japan reported that the average age at the onset of AOSD was 38.1±14.3 years old in 1994 (47), in contrast to 46±19 years old in 2010 (44). Another report in 2016 from Japan stated that the mean onset age was 53.1± 19.6 years old (4). About 23% of cases developed it at !…”
Section: Discussionmentioning
confidence: 99%
“…65 years old and about 16% at ! 75 years old (4). This has been attributed to the marked aging of the population now occurring in Japan (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Supportive measures, which could include platelet transfusion, coagulation factors (or fresh frozen plasma), and fibrinogen (in cryoprecipitate) infusion to control severe bleeding or sometimes heparin if no active bleeding is present [70]. 2.…”
Section: Coagulation Disordersmentioning
confidence: 99%
“…The estimated prevalence of AOSD is 0.14‐0.40 per 100 000 persons . Although the onset is described to be predominant in young adults, a recent study in Japan showed no distinct peak age, with a mean age at onset of 53.1 years, and slight female predominance (64.1%) . The diagnostic criteria are shown in Table .…”
Section: Introductionmentioning
confidence: 99%